Analysis of the Issuance of Government Regulation in Lieu of Law (PERPPU) Number 2 Year 2022 in the Perspective of Law Formation Politics - Zulwisman, Zulwisman; Diegio, Muhammad Haikal (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
This study aims to examine and analyze the issuance of government regulations in lieu of law (Perppu) no. 2 of 2022 in the political perspective of forming laws. PERPPU is in the form of a Government Regulation (PP), the substance of which is the same as the Law. As a legal product in a material sense, the House of Representatives is tasked with closely monitoring the PERPPU that is issued and enforced. The research method used is normative juridical with statutory, conceptual and comparative approaches. The results of the discussion of this research are based on the Constitutional Court Decision Number 91/PUU XVIII/2020, the conditions listed in the preamble, taking into account the Government Regulation in Lieu of Perppu Law Number 2 of 2022 Concerning Job Creation, and the political climate considering the tiered stages of the 2024 Pilkada , it is determined that with the issuance of PERPPU Number 2 of 2022 Concerning Job Creation, the three conditions set forth in the Constitutional Court Decision have been fulfilled.